ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR BADUNG KOTA DENPASAR : STUDI SEBELUM DAN SESUDAH DI RELOKASI - Adi Putra, Komang Gede Candra; Dewi, Made Henny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 6, Juni 2018 (pp. 1112-1351), 2018)
Badung market hit by fire accident in February 2016 ago. The largest market in Denpasar City became paralyzed instantly and the government imposed a relocation policy of Badung Market traders. Selected location is Ex Supermarket Tiara Grosir Banjar Balun Denpasar. The purpose of this study is to determine the effect of working capital, working hours and length of business simultaneously and partially to income, and to determine whether there is a decrease in income before and after relocated. Primary data with quantitative methods in the form of associative in use in this study. The sample in this research is the market trader of Badung City Denpasar as many as 90 people, sampling technique with accindental sampling method. The analysis technique used is multiple linear regression analysis. Based on the results of the study showed that simultaneously and partially working capital, working hours and length of business significantly influence the income of Badung Market traders in Denpasar, while relocation has no significant effect on income. The decline in merchant revenue after the relocation is due to the physical and non-physical condition of the Ex Supermarket Tiara Grosir.   Keywords : working capital, working hours, length of business, relocation, income